HAM dalam Perspektif Kriminologi: Eksploitasi Buruh Sebagai Bentuk Perbudakan Modern - ; Arristo Herbawono (Syntax Idea)
Exploitation of the working class or labor is one form of modern slavery, where workers often have their labor squeezed to maximize the profits of capital owners, with wages that do not equate to the sweat they put in. Despite this, labor exploitation often doesn't receive attention and tends to be overlooked, because exploitation is an integral part of the capitalist economic system and will continue to exist as long as that economic system is in place, leading to a gradual normalization of exploitation. This article will discuss the relationship between modern slavery and labor exploitation, and why modern slavery is often disregarded, particularly in human rights issues. Furthermore, this article will provide an understanding of the importance of criminology in addressing human rights issues, especially modern slavery.